Online instructional effort measured through the lens of teaching presence in the community of inquiry framework: A re-examination of measures and approach - Peter Shea (Athabasca University Press, 2010)
With more than 4 million students enrolled in online courses in the US alone (Allen & Seaman, 2010), it is now time to inquire into the nature of instructional effort in online environments. Reflecting the community of inquiry (CoI) framework (Garrison, Anderson, & Archer, 2000) this paper addresses the following questions: How has instructor teaching presence (Anderson, Rourke, Garrison, & Archer, 2001) traditionally been viewed by researchers? What does productive instructor effort look like in an entire course, not just the main threaded discussion? Results suggest that conventional research approaches, based on quantitative content analysis, fail to account for the majority of teaching presence behaviors and thus may significantly under represent productive online instructional effort.